Start-Up Team with Maps and Model of SMU's Campus (Institutional Knowledge at Singapore Management University, 1998)
Members of the planning team for the new Singapore Management University posing with maps and a three-dimensional model of the planned city campus. Left to right: Associate Professor Leong Kwong Sin, Wang Wai Yee, Associate Professor Toh Tian Ser, Associate Professor Low Aik Meng, Professor Tan Teck Meng, Professor Tan Chin Tiong, Eddie Wee, and Grace Cheng. Photo taken at SIM on 5 December 1998.